Patient safety culture: radiographers’ perception - Ribeiro, Luís Pedro (2022)
Research to evaluate radiographers’ perceptions about patient safety culture in Portuguese public and private imaging facilities found that overall perception is positive but the safety culture dimensions rating should guide culture development of safety culture improvement action plans.